Respuesta :
So, r' (the new r) becomes kr, and h'=h*k,
so V' = pi * (r')^2*h' = pi * (r*k)^2*(h*k) = pi*r^2*h*k^3 = V * k^3
Convinced?
so V' = pi * (r')^2*h' = pi * (r*k)^2*(h*k) = pi*r^2*h*k^3 = V * k^3
Convinced?
Answer:
The answer in the procedure
Step-by-step explanation:
we know that
If two figures are similar, then the ratio of its corresponding sides is equal to the scale factor
so
[tex]k=r'/r[/tex] and [tex]k=h'/h[/tex]
The volume of the original cylinder is equal to
[tex]V=\pi r^{2}h[/tex]
If the cylinder is scaled proportionally by a factor of k
then
the new radius is ------> [tex]r'=kr[/tex]
the new height is ------> [tex]h'=kh[/tex]
The volume of the scaled cylinder is equal to
[tex]V'=\pi r'^{2}h'[/tex]
substitute the values
[tex]V'=\pi (kr)^{2}(kh)[/tex]
[tex]V'=(k^{3})\pi r^{2}h[/tex]
Remember that
[tex]V=\pi r^{2}h[/tex]
so
substitute
[tex]V'=V(k^{3})[/tex]
The volume of the scaled cylinder is equal to the scale factor elevated to the cube multiplied by the volume of the original cylinder